PELUANG DAN TANTANGAN FINTECH LENDING DALAM EKOSISTEM KEUANGAN GLOBAL: SYSTEMATIC LITERATURE REVIEW: Opportunities And Challenges Of Fintech Lending In The Global Financial Ecosystem: A Systematic Literature Review - Artha, I Wayan Budi; Antari, Ni Luh Sili; Santika, I Putu (Ganec Swara, 2026)
Fintech lending has become a significant innovation that is transforming the global financial system by improving access to credit, operational efficiency, and financial inclusion. This study aims to identify the opportunities and challenges of fintech lending within the global financial ecosystem using a Systematic Literature Review (SLR) approach on 45 scientific articles published between 2017 and 2025. The analysis was conducted through thematic classification to identify key patterns, opportunities, challenges, and implications for future research. The results indicate that the primary opportunities for fintech lending lie in the growth of the digital ecosystem and the enhancement of financial inclusion, particularly for groups underserved by traditional financial institutions. The use of technologies such as artificial intelligence (AI), big data, and automation has proven to improve the accuracy of credit risk assessment, operational efficiency, and service scalability. Additionally, collaboration between fintech and traditional financial institutions strengthens the integration of digital financial systems. However, fintech lending also faces challenges, particularly regarding credit risk management, data security, consumer protection, and dynamic regulations. Information asymmetry and algorithmic bias risks can affect system stability. This study concludes that fintech lending has great potential to enhance financial inclusion, but requires adaptive regulation, effective risk management, and responsible technology integration to ensure the sustainability of the digital financial ecosystem.